Towards a Realist Sociology of Education: A Polyphonic Review Essay. Issue 2 (14th November 2017) - Grenfell, Michael; Hood, Susan; Barrett, Brian D.; Schubert, Dan
Abstract: This review essay evaluates Karl Maton's Knowledge and Knowers: Towards a Realist Sociology of Education as a recent examination of the sociological causes and effects of education in the tradition of the French social theorist Pierre Bourdieu and the British educational sociologist Basil Bernstein. Maton's book synthesizes the scholarship of Bourdieu and Bernstein and complements their work with "discoveries" from the world of systemic functional linguistics to produce a new "realist sociology of education." It does so by means of Legitimation Code Theory, defined as a "toolkit" to analyze knowledge construction in cultural fields, especially education. The authors of this review essay take a polyphonic approach in assessing this ambitious synthesis, offering four perspectives on Maton's book. Brian Barrett provides a Bernsteinian perspective; Dan Schubert approaches the book from his grounding in Bourdieu; and Susan Hood contributes a view from systemic functional linguistics. Michael Grenfell weaves these three perspectives together and provides introductory and concluding reflections. They aim, through their combined expertise, to use Maton's book as an occasion to take stock of the state of the field of sociology of education generally and to reflect on the questions: What is its nature and what type of knowledge does it express? To what uses may it be set and what is its place within the larger project of educational theory?